Howzzat? - Barua, S. K. (SAGE Knowledge. Cases., 2015)
In 2015 a match-fixing scandal rocked the Indian cricket world. High-ranking members of teams and cricket's ruling body were implicated in betting based on match-fixing and insider knowledge. The president of the governing association was accused, but avoided any definitive judgment. The Indian cricket world must figure out how to proceed, and what reforms must take place to prevent such a thing from happening again.